Digital nursing and midwifery leadership: Protocol for a multi-method exploration of policy implementation and impact on practice in the WHO European Region - Gillian Janes; Lorna Chesterton; Joanne Reid; Vanessa Heaslip; Michael Shannon; Bente Lüdemann; Rolf-André Oxholm; João Gentil; Clayton Hamilton; Natasha Phillips (PLoS ONE, 2025)
Background Digital health is redefining nursing and midwifery practice, fuelled by national and international priorities for health improvement and workforce planning. Developing digitally enabled healthcare systems can help enable universal health coverage and improve safety outcomes while offering solutions to workforce shortages. However, research suggests that nursing/midwifery leaders are often absent from the strategic planning, design, and implementation of digitally enabled healthcare service models and the associated technological systems that directly impact practice. Objectives This paper presents the protocol for a sequential, multi-method exploration of digital health policy implementation and its impact on practice. This investigation from the perspective of national nursing/midwifery leaders, will increase understanding of the impact these professions have on national decision-making, which will be used to inform digital healthcare policy implementation and development across Europe and beyond. Methods A purposive sample of national nursing/midwifery leaders across the WHO European region will be recruited. In Phase 1, individuals will be invited via email to participate in an anonymous online survey, with findings used to inform the topic guide for online focus groups in Phase 2. Descriptive statistical analysis of the survey dataset will be used to understand the range of countries, roles, contexts, participant experiences, and perceptions on which the findings are based. Where possible, analysis will be undertaken, e.g., by country, and participant role to identify any patterns, gaps, and key areas for further exploration during Phase 2. Survey respondents will be offered the opportunity to participate in an online focus group. Free text questions from the survey and data from focus groups will be transcribed verbatim and analysed using a reflexive thematic approach. Discussion The study outlined within this paper will generate empirical data on to what extent and how national nursing/midwifery leaders influence the progress of digital healthcare, based on their experiences implementing key European policy. In gaining a better understanding of this policy implementation, and the role played by nursing and midwifery leaders, the factors that facilitate or hinder this process can be identified and better managed, to maximise the benefits of digital healthcare for population outcomes moving forward. Ethical approval Ethical approval for this study was granted on 10.12.25 by Anglia Ruskin University [ID ETH2425−0725]